Determinants of whistleblowing implementation in EU countries on the example of the Polish public sector experience - Agnieszka SKOCZYLAS-TWOREK (Communications of International Proceedings, 2025)
The growing scale of abuse, fraud, and irregularities contributes to the development of tools aimed at limiting them. One such tool is legal regulations related to the implementation of whistleblowing systems. This is addressed by the provisions of the EU Whistleblowers Directive, which obliged EU countries to implement this tool into national law. Due to numerous delays, this implementation was finally completed in 2025. Hence, only a few studies on the implementation of this tool have been conducted so far. The aim of the publication was to fill this gap to some extent by analyzing the implementation of selected provisions of EU Directive 2019/1937 into the national law of EU countries. In addition, using the example of one country, the effectiveness of the organization of the whistleblowing system in selected entities required by law to establish it was assessed. The methodology used was based on a quantitative and qualitative analysis aimed at verifying whether Member States had not only implemented selected provisions of the Directive, but also what individual solutions they had adopted in this regard. The results of the analysis showed that the adopted legal regulations on whistleblowing at the level of EU countries are not exhaustive and leave actors free to shape them. The Directive provides an excellent premise for laying the foundations for the development of the whistleblowing tool in EU countries, however, it is necessary to take the right approach to its implementation, not limiting it to the adoption of a minimum framework only, but to expand its scope of action and protection at the national level, so that it is an effective tool for reducing widespread violations of the law, unethical and corrupt behavior at both the organizational and state levels.
Keywords: whistleblowing; whistleblower; legal violations